1984
DOI: 10.20506/rst.3.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Two serotypes of Corynebacterium pseudotuberculosis isolated from different animal species

Abstract: Hyperimmune sera against four strains of Corynebacterium pseudotuberculosis isolated from different animals (sheep, goat, buffalo and cattle) were obtained by inoculating rabbits with strains in different forms (live, dead plus live or dead). Immunization with live or dead bac teria followed by live strains gave similar results with regard to antibody titres and number of precipitin lines. Typing 21 strains of C. pseudotuberculosis by specific precipitin reac tions in agar gel was performed by using antigens e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 1 publication
0
45
0
Order By: Relevance
“…2) having the same high titer of SH but produced half the amount produced by isolate No. (1). at the same time, strain No.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) having the same high titer of SH but produced half the amount produced by isolate No. (1). at the same time, strain No.…”
Section: Discussionmentioning
confidence: 99%
“…Biotypes were determined by conventional tests as described previously (1) in addition to starch hydrolysis.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the broad host spectrum, natural cross-species transmission of C. pseudotuberculosis between small ruminants and cattle does not appear to occur [12], although infections of cattle with both biovars have been previously reported [31].…”
Section: Introductionmentioning
confidence: 98%
“…Strains that reduce nitrate are referred as biotype equi and strains that fail to do so are referred as biotype ovis. Barakat et al (1984) found two serotypes referred as type I and type II which corresponded with nitrate reductase negative and positive strains, respectively. In camels, only the serotype I (biotype ovis) has been described in the available literature (Wernery and Kaaden 2002).…”
Section: Introductionmentioning
confidence: 96%